2021
DOI: 10.1088/1755-1315/830/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

The Vulnerability of Settlements in The Areas Impacted by Lapindo Mudflow Disaster, Sidoarjo

Abstract: The Lapindo Hot Mudflow Disaster is a disaster case that occurred in 2006 in Sidoarjo Regency, East Java, and has become a hot issue at the national, even international level. After 14 years, it turns out that until now the impact of the disaster has not completely subsided. The settlements that were impacted by the mudflow disaster but still inhabited by the community looked vulnerable because many were damaged, cracked and the floors slowly subsided due to land subsidence. This study aims to determine the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Regarding the changes in land use in the three villages that became this study's sites (Figure 2 Based on the data from the satellite imagery of land area changes in the area impacted by the Lapindo mudflow disaster, it was found that: the area of settlements and paddy fields decreased (Figure 3), while the area of water bodies, mud, vacant land and mud embankments increased significantly (Ekawati et al 2020). This shows that the levels of disaster risk and vulnerability of the community settlements in the area affected by the Lapindo mudflow disaster are high and they require more attention (Ekawati and Sulistyowati 2021). Moreover, based on the 2017 situation, to the east of the mud embankment wall, there are still water bodies that have begun to inundate the locations around the community settlement in Glagaharum Village, so it is feared that the expansion of the mud embankment will be carried out again by the PPLS (the Sidoarjo Mudflow Management Center).…”
Section: Land Use Changementioning
confidence: 97%
“…Regarding the changes in land use in the three villages that became this study's sites (Figure 2 Based on the data from the satellite imagery of land area changes in the area impacted by the Lapindo mudflow disaster, it was found that: the area of settlements and paddy fields decreased (Figure 3), while the area of water bodies, mud, vacant land and mud embankments increased significantly (Ekawati et al 2020). This shows that the levels of disaster risk and vulnerability of the community settlements in the area affected by the Lapindo mudflow disaster are high and they require more attention (Ekawati and Sulistyowati 2021). Moreover, based on the 2017 situation, to the east of the mud embankment wall, there are still water bodies that have begun to inundate the locations around the community settlement in Glagaharum Village, so it is feared that the expansion of the mud embankment will be carried out again by the PPLS (the Sidoarjo Mudflow Management Center).…”
Section: Land Use Changementioning
confidence: 97%
“…The mud continued to leak from the ground with no sign of stopping, inundating the surrounding area with thick mud. This mudflow has been ongoing for some time and is expected to continue for some time (Wibowo et al, 2018) and (Ekawati & Sulistyowati, 2021). In its early days, the outburst rates ranged between 100.000 and 120.000 m 3 per day, with an estimated temperature of 100 degrees Celsius (Sidoarjo, 2020).…”
Section: Sidoarjo East Java Province 2006mentioning
confidence: 99%
“…Soon after, the mud inundated nearby villages. According to the most recent report in 2020, the mudslide affected 16 villages in three districts in Porong, Tanggulangin, and Jabon, inundating more than 6,5 km2 of land with a depth of nearly 25 meters and displacing more than 40.000 people (Kure et al, 2014), (Ekawati & Sulistyowati, 2021) and (Ekawati et al, 2020). The inundated area included industrial estates, agricultural areas, the Surabaya-Gempol toll road, and densely populated residential regions.…”
Section: Sidoarjo East Java Province 2006mentioning
confidence: 99%
See 1 more Smart Citation